2021
DOI: 10.3892/mmr.2021.12027
|View full text |Cite
|
Sign up to set email alerts
|

Long non‑coding RNA OIP5‑AS1 facilitates the progression of ovarian cancer via the miR‑128‑3p/CCNG1 axis

Abstract: long non-coding rna (lncrna) o-phthalaldehydeinteracting protein 5 antisense transcript 1 (oiP5-aS1) serves major roles in the progression of various types of cancer. The present study investigated its biological function in ovarian cancer (oc) and its mechanisms. The levels of oiP5-aS1, microrna-128-3p (mir-128-3p) and cyclin G1 (ccnG1) were examined by reverse transcription-quantitative Pcr. cell viability, apoptosis, migration and invasion were detected to analyze cellular progression. Glycolytic metabolism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…CCNG1 has been reported to participate in the pathogenesis of human diseases by mediating lncRNA or miRNA. For example, lncRNA OIP5-AS1 promoted the progression of ovarian cancer by regulating CCNG1 [ 11 ]. MiR-122-5p inhibited cell proliferation, migration, and invasion by targeting CCNG1 in pancreatic ductal adenocarcinoma [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…CCNG1 has been reported to participate in the pathogenesis of human diseases by mediating lncRNA or miRNA. For example, lncRNA OIP5-AS1 promoted the progression of ovarian cancer by regulating CCNG1 [ 11 ]. MiR-122-5p inhibited cell proliferation, migration, and invasion by targeting CCNG1 in pancreatic ductal adenocarcinoma [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…33 More importantly, miR-324-3p in ovarian cancer also confers an antitumor effect, and its effect was abolished when lncRNA-OIP5-AS1 acts as a sponge through competitive binding. 34 Moreover, our study furthered the mechanistic understanding and delineated that DPP10-AS1 competitively bound to miR-324-3p and thus upregulated the expression of tumor-supporting CLDN3. The migration distance and invasion ability of PC cells were diminished after the silencing of CLDN3.…”
Section: Discussionmentioning
confidence: 53%
“…Currently, OIP5-AS1 has been determined to overexpress in epithelial OC and depletion of OIP5-AS1 contributes to limit cellular aggressiveness and EMT process [28]. Moreover, Q-Y Liu et al have defined OIP5-AS1 with oncogenic property in OC and found that OIP5-AS1 knockdown represses OC cell viability, invasion, and migration [29]. A recent publication has uncovered that miR-92a-3p suppressed cell growth in Wilms' tumor [30].…”
Section: Discussionmentioning
confidence: 99%